1990
DOI: 10.1002/1097-0142(19900501)63:9<1714::aid-cncr2820630912>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin stimulates growth of human prostatic cancer cellsin vitro

Abstract: Cell proliferation of the human prostatic carcinoma cell line PC3 and of the epithelial cell strain PMU 23 derived from a primary culture of a stage III prostatic carcinoma was enhanced dose dependently by adding 0.1 nM to 10.0 nM bombesin (BMBS) to the culture medium. The growth stimulation was specifically inhibited by antibodies versus Gastrin Releasing Peptide (GRP) crossreacting with BMBS. Presence of BMBS-positive neuroendocrine cells in human prostate and measurable amounts of BMBS-like peptides in pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
107
1
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(114 citation statements)
references
References 21 publications
0
107
1
6
Order By: Relevance
“…2 It has been shown that the receptor for bombesin/GRP was expressed in prostate cancer cell lines and that the proliferation of PC-3 prostate cancer cells was significantly enhanced by bombesin in vitro. 18,19 Bombesin was also observed to increase the invasive capacity of PC-3 prostate cancer cells, 4 and stimulated the secretion of MMP-9 and an increase of urokinase-type plasminogen activator (u-PA) activity. 20 Our previous and present studies have demonstrated that GRP enhanced the invasion of both PC-3 and DU-145 cells to Matrigel and the haptotactic migration of PC-3, DU-145, TSU-pr1 and LNCaP cells to fibronectin, but it had no effect on either the gelatinolytic activities of MMP-9 or fibrinolytic activities of u-PA in fibrin zymography of PC-3 and DU-145 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2 It has been shown that the receptor for bombesin/GRP was expressed in prostate cancer cell lines and that the proliferation of PC-3 prostate cancer cells was significantly enhanced by bombesin in vitro. 18,19 Bombesin was also observed to increase the invasive capacity of PC-3 prostate cancer cells, 4 and stimulated the secretion of MMP-9 and an increase of urokinase-type plasminogen activator (u-PA) activity. 20 Our previous and present studies have demonstrated that GRP enhanced the invasion of both PC-3 and DU-145 cells to Matrigel and the haptotactic migration of PC-3, DU-145, TSU-pr1 and LNCaP cells to fibronectin, but it had no effect on either the gelatinolytic activities of MMP-9 or fibrinolytic activities of u-PA in fibrin zymography of PC-3 and DU-145 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Bombesin and calcitonin each exert a proliferative effect on the androgen-independent PC-3 and DU-145 prostate cancer cell lines (Bologna et al, 1989;Jongsma et al, 2000;Larran et al, 2000), as well as stimulation of PC3 cell migration (Aprikian et al, 1997). Cell growth and DNA synthesis are increased when prostate cancer cells are stimulated with PTHrP (Iwamura et al, 1994;Tovar-Sepulveda and Falzon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and preclinical data have indicated a mitogenic role for small regulatory peptides such as endothelin-1 (ET-1), bradykinin, bombesin-like peptides and neurotensin in various stages of prostate cancer (Bologna et al, 1989;Papandreou et al, 1998). Endothelin-1, in particular, has been demonstrated in prostatic tissue in vivo and in human PC lines in vitro with plasma ET-1 concentrations significantly elevated in men with metastatic disease (Nelson et al, 1995).…”
mentioning
confidence: 99%